Manhaj Muʿjam al-Munawwir li-Aḥmad Warson Munawwir wa Muʿjam li-Maḥmūd - Ahmad Kali Akbar (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2015)
Al-Munawwir Dictionary by Aḥmad Warson Munawwir is one of the most significant Arabic dictionaries that has played an important role in the teaching and learning of Arabic for non-native speakers. It contains a wide range of contemporary Arabic vocabulary suitable for both university and non-university students. Another widely recognized Arabic dictionary is the Arabic–Indonesian Dictionary by Dr. Maḥmūd Yūnus, which is well known for its simplicity. It is commonly used by elementary and junior secondary students in Islamic schools and boarding schools. One of its major advantages is the ease with which users can locate lexical entries, as the dictionary is organized according to the standard alphabetical order, making it particularly suitable for beginners. Undoubtedly, each of these dictionaries employs its own distinctive lexicographical methodology, differing in various aspects such as the number of entries, the presentation of meanings, and other organizational features. From this perspective, the author considers it important to conduct a comparative study of the methodologies adopted by these two dictionaries in order to identify their respective characteristics and unique strengths. This study does not aim to determine which dictionary is superior. Rather, it seeks to examine the limitations and advantages of each dictionary so that future lexicographical works may benefit from their strengths and ultimately produce dictionaries that are more comprehensive and effective.